Pleomorphic Adenoma of an Ectopic Lacrimal Gland in the Eyebrow - Gurvinder Kaur; Jacob Koshy; Satish Thomas; S.M. Bhatti (Delhi Journal of Ophthalmology)
This is a case report of an unusual presentation of an ectopic lacrimal gland in the region of the eyebrow. The tumour was removed surgically and histopathology revealed the tissue to be a pleomorphic adenoma. To the best of our knowledge, this is the first reported case of ectopic lacrimal tissue at this site.